Structural properties and anti-inflammatory activity of purified polysaccharides from Hen-of-the-woods mushrooms (Grifola frondosa) - Liu, Xiaoyi; Chen, Shuai; Liu, Huijuan; Xie, Jiao; Hasan, K. M. Faridul; Zeng, Qibing; Wei, Shaofeng; Luo, Peng (Frontiers in Nutrition, 2023)
Grifola frondosa is an edible medicinal mushroom whose main active ingredient is polysaccharide and has been proved to have a variety of health benefits. In this study, ultrasonic-assisted extraction method was used to obtain crude Grifola frondosa polysaccharides (GFP) after purification, the optimum extraction conditions were as follows: extraction time 71 min, extraction temperature 90 ℃, solid-liquid ratio 1:37 g/ml, and ultrasonic power 500W. Under the optimum conditions, the predicted yield of polysaccharide was 21.72%. GFP was obtained after purification by DEAE-52 and Sephadex G-100. The structural characterization of GFP was elucidated using Fourier Transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), Ion Chromatography (IC), Ultraviolet visible photometer (UV), Thermogravimetric-differential scanning (TG-DSC) and Congo red experiments. And morphological analysis was performed using Scanning Electronic Microscopy (SEM). The results showed that the polysaccharide composition was fucose: glucosamine hydrochloride: galactose: glucose: mannose with a molar ratio of 0.025, 0.004, 0.063, 0.869, and 0.038. We found that GFP had typical absorption peak and the GFP extracted by ultrasound-assisted extraction protocol was mainly β-glucan. In addition, the therapeutic effect of GFP to Oxazolone (OXZ)-induced ulcerative colitis (UC) in mice was also studied. Therefore, OXZ-induced UC mice was treated with three different doses of GFP (80160 and 320 mg/ kg body weight) or Sulfasalazine (SASP) as one of the positive controls (370 mg/ kg). It was found that GFP could prevent weight loss in mice. After treatment, the mice were sacrificed, the blood samples and colon tissue samples were collected. It was found that GFP could prevent the decrease of colon length and decrease the levels of leukocytes, platelets and neutrophils in UC mice. Moreover, GFP also decreased the expression of proinflammatory cytokines (tumor necrosis factor (TNF)-α, interleukin (IL)-1 β), increased IL-10 and reduced colon injury in UC mice. Therefore, ultrasound-assisted extraction of GFP can reduce OXZ-induced intestinal inflammation, thus become a promising candidate for the treatment of UC and have the potential to be developed as a food supplement to improve intestinal diseases.